Review on antimicrobial combination of sulbactam/durlobactam - Nguyen, Thị Thu Thuỷ; Huynh, Lời (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
Sulbactam/durlobactam, is a co-packaged antibacterial drug that was approved for the treatment of infections caused by Acinetobacter baumannii-calcoaceticus complex. Co-administration of durlobactam with sulbactam prevents sulbactam degradation by β-lactamases. In May 2023, this β- lactam/β-lactamase inhibitor combination was approved in the United States of America for use in patients 18 years of age and older for the management of hospital-acquired bacterial pneumonia and ventilator-associated bacterial pneumonia caused by susceptible isolates of Acinetobacter baumanniicalcoaceticus complex. This review summarizes the mechanism, clinical studies, pharmacology, and interaction of sulbactam/durlobactam